Rizal without the overcoat - Ocampo, Ambeth R. (Anvil, 2008)
"An updated and expanded edition of the best-selling title that offers fresh insights on the life and times of our National Hero. Here, Ocampo has succeeded where other historians have failed-- and that is in making the study and reading of Rizal not a burden, but a joy."--Publisher's description.